(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Miscarriages account for about one in six/one in seven pregnancies, and probably over one in five excluding induced abortions, i.e. over 20 million events per year. However, any precise and valid estimate is made difficult by uncertainties in diagnosis, ascertainment, distinction in registration between induced and spontaneous abortions, and certification. These uncertainties vary across geographic region, country and socio-economic status...